How unit price awareness and usage encourages grocery brand switching and expenditure. (July 2019) - Mortimer, Gary; Weeks, Clinton S.
Abstract: Previous research has suggested that unit price information encourages shoppers to switch to the cheapest products available to reduce grocery expenditure, something that is rarely a commercial goal for retailers or manufacturers. Further, past unit pricing research has largely not considered other factors, like brand dominance or the range of product alternatives available within a category, despite these being likely to influence switching behaviour. Accordingly, this current study examines longitudinal field experiment data to explain how unit prices impact brand switching and overall grocery expenditure. In contrast to the commonly held belief that consumers 'save' money once educated about unit pricing, findings demonstrate shoppers select mid-range unit priced products and reinvest 'savings' back into their weekly grocery budget. Further, our results also show substantial product category differences in switching behaviour. The study offers theoretical insights and important practical implications for retailers and product manufacturers.